Stabilization of track substructure with geo-inclusions—experimental evidence and DEM simulation. Issue 2 (3rd April 2017) - Ngo, Ngoc Trung; Indraratna, Buddhima; Rujikiatkamjorn, Cholachat
ABSTRACT: This article reviews on current knowledge of rail track geomechanics, including several important concepts and topics related to laboratory testing and computational modelling, to study the shear stress-strain and deformation of ballast improved by geosynthetics and recycled rubber mats. The effect that impact loads have on ballast degradation and its mitigation due to resilient synthetic mats (i.e. rubber mats) between the ballast and the subballast is investigated using large-scale impact-testing apparatus. Computational modelling with finite element and discrete element methods are increasingly being used to model ballasted tracks reinforced with geosynthetics to capture the continuum media of formation soils and the discrete nature of ballast aggregates. The article focuses on reviewing previous studies by the University of Wollongong on ballasted track substructure and highlights some practical implications whereby innovation progresses from theory to practice.